Surrogate reference standards in quantitative high performance liquid chromatography; a case study of the analysis of Piroxicam Capsules and Metronidazole Tablets - Owusu, Nicholas Amoah (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Science in Analysis and Quality Control